By the Principle of Duality, we need only prove the first statement in each part.
(1) By definition \(a \vee b\) is the least upper bound of \(\{ a, b\}\text{,}\) and \(b \vee a\) is the least upper bound of \(\{ b, a \}\text{;}\) however, \(\{ a, b\} = \{ b, a \}\text{.}\)
(2) We will show that \(a \vee ( b \vee c)\) and \((a \vee b) \vee c\) are both least upper bounds of \(\{ a, b, c \}\text{.}\) Let \(d = a \vee b\text{.}\) Then \(c \preceq d \vee c = (a \vee b) \vee c\text{.}\) We also know that
\begin{equation*}
a \preceq a \vee b =d \preceq d \vee c = (a \vee b) \vee c\text{.}
\end{equation*}
A similar argument demonstrates that \(b \preceq (a \vee b) \vee c\text{.}\) Therefore, \((a \vee b) \vee c\) is an upper bound of \(\{ a, b, c \}\text{.}\) We now need to show that \((a \vee b) \vee c\) is the least upper bound of \(\{ a, b, c\}\text{.}\) Let \(u\) be some other upper bound of \(\{ a, b, c \}\text{.}\) Then \(a \preceq u\) and \(b \preceq u\text{;}\) hence, \(d = a \vee b \preceq u\text{.}\) Since \(c \preceq u\text{,}\) it follows that \((a \vee b) \vee c = d \vee c \preceq u\text{.}\) Therefore, \((a \vee b) \vee c\) must be the least upper bound of \(\{ a, b, c\}\text{.}\) The argument that shows \(a \vee ( b \vee c)\) is the least upper bound of \(\{ a, b, c \}\) is the same. Consequently, \(a \vee ( b \vee c) = (a \vee b) \vee c\text{.}\)
(3) The join of \(a\) and \(a\) is the least upper bound of \(\{ a \}\text{;}\) hence, \(a \vee a = a\text{.}\)
(4) Let \(d = a \wedge b\text{.}\) Then \(a \preceq a \vee d\text{.}\) On the other hand, \(d = a \wedge b \preceq a\text{,}\) and so \(a \vee d \preceq a\text{.}\) Therefore, \(a \vee ( a \wedge b) = a\text{.}\)